Evolutionary dynamics and genomic features of the Elizabethkingia anophelis 2015 to 2016 Wisconsin outbreak strain - Amandine Perrin (Nature Portfolio, 2017)
Elizabethkingia anophelis is an emerging pathogen of high antimicrobial resistance. Perrin and colleagues sequenced isolates of a 2015/2016 E. anophelis outbreak in Wisconsin and found substantial genetic diversity, accelerated evolutionary rate and a disruptive mutation in the DNA repair gene mutY.